(untitled) (Journal of Educational Sciences, 2026)
In light of the increasing need to ensure the quality of work-integrated learning, it is essential to assess the effectiveness of the approaches implemented in various formats and learning conditions. Existing theoretical models for work-integrated learning have enabled the development of significant evaluation metrics, ensuring quality assessment and the selection of the most relevant approaches to learning. The effectiveness of the implemented approaches to work-integrated learning was assessed using metrics such as student satisfaction with learning formats, the impact of company-requested projects on the successful completion of work-integrated learning programs, the impact of additional certification courses on the completion of the work-integrated learning program and the impact of work-integrated approaches on the employment of work-integrated program graduates. To evaluate work-integrated programs based on these metrics, a marketing research method was used in the form of a student survey, which defined an integral performance indicator based on student satisfaction results. 252 students from the republic took part in the study. A qualitative content analysis method was used to analyze student satisfaction in more detail. This survey identified barriers to quality applied learning. The study based on these metrics has shown that increasing projects at companies’ request is necessary, using virtual and simulation educational technologies and expanding the range of learning through additional courses and certification, allowing students to obtain multidisciplinary competencies. The proposed metrics can be used to update educational programs and expand evaluation methods and learning formats of cooperation between universities and companies. The identified metrics will allow for a more accurate and correct assessment of the competitiveness of work-integrated programs. Keywords: work-integrated learning, metric, satisfaction, project, course, employability.